A CMIP6 LUMIP analysis of historical and projected climate impacts of land use and land cover changes in the United States - Lin, Yen-Heng; Fosu, Boniface; He, Jie; Dyer, Jamie L.; Ambinakudige, Shrinidhi; Bowman, Caleb; Violett, Brett (Frontiers in Environmental Science, 2026)
Land use and land cover changes (LULCCs) are drivers as well as outcomes of climate change, yet their impacts remain among the most uncertain aspects of climate projections. This uncertainty stems, in part, from the limited experiments focusing on LULCC-related feedbacks, compared to the plethora of established frameworks for quantifying uncertainties in the atmospheric and oceanic components of global climate models. This study investigates the effects of LULCC on climate changes in the contiguous United States by leveraging a hierarchy of simulations from the Coupled Model Intercomparison Project (CMIP6) Land Use Model Intercomparison Project (LUMIP) under various LULCCs. While local increases in cropland and grazing land have directly cooled the Midwest and northern Great Plains since the industrial era, precipitation changes are largely driven via LULCC’s interaction with the large-scale circulation. Other U.S. regions exhibit distinct LULCC impacts that are highly dependent on specific geographic and environmental conditions. Distinct and often opposing changes in regional climate are observed between projections with sustainable versus unsustainable land use. This study underscores the importance of LULCC not only in shaping regional climate projections across the U.S., but also for developing both regional and global climate adaptation strategies and policies.